POTENTIAL BENEFIT OF PURSLANE HERBS (PORTULACA GRANDIFLORA) EXTRACT IN WOUND HEALING - Antonius Budiawan; Levi Puradewa; Agus Purwanto; Bida Cincin Kirana (European Journal of Humanities and Educational Advancements, 2024)
Chronic wound infection is a global problem, especially in developing countries with limited health access. Medicinal plants are materials that are affordable and safe for wound care from natural sources. Several plants have been studied for their benefits in wound healing and one of them is purslane (Portulaca grandilfora). In various studies, the purslane extract concentration in wound healing activity is not fully understood. This research aimed to determine wound healing effective dose of purslane herbs (Portulaca grandilfora) magenta flower variety extract on rabbit’s skin. This was experimental research that used wound-induced rabbits. Wounds were grouped into 5 groups such as negative (aqua destilata) (K-) and positive (betadine solution) (K+) control groups, 25% (D1), 50% (D2), and 75% (D3) extract concentration dosage form groups. The result showed that all extract-treated groups wound healed faster than the negative control group. Purslane herbs (Portulaca grandilfora) magenta flower variety 50% and 75% concentration dose showed wound healing activity which significantly differents from negative control on day-11 and day-12 for 25% concentration dose. Based on the research results, purslane extract (Portulaca grandiflora) has potential benefits in wound healing. The 50% concentration of extract of puslane (Portulaca grandiflora) is the effective concentration dosage form in wound healing activity